ANALISIS MEKANISME PERHITUNGAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 25 PADA CV ANGGREK JINGGA PEKALONGAN - Kusuma Wijaya; Anni Safitri; Noviana Widya Ningsih (Politeknik Negeri Semarang, 2021)
The purpose of this study was to determine the mechanism for calculating and reporting income tax article 25 at CV Anggrek Jingga. CV Anggrek Jingga is a company engaged in the printing sector specializing in the procurement of government goods and services that was established in 2019 and has not calculated and reported income tax article 25 to the Directorate General of Taxes (DGT). The research method used is a qualitative method and data collection techniques by interviewing the owner of CV Anggrek Jingga and documentation in the form of an income statement for 2020. The calculation mechanism by analyzing the income statement, calculating income tax articles 21, 22, and 23 to then the result as a deduction from the results of taxable income. The results of this study indicate that CV Anggrek Jingga has not calculated and reported income tax article 25 which the calculation is carried out during the 2020 tax year by subtracting income tax credits such as income tax articles 21, 22, and 23. Reporting on CV Anggrek Jingga This is done through the online e-filling application system to the Directorate General of Taxes (DGT).